Vertical-horizontal permeability correlations using coring data - Shedid A. Shedid (Egyptian Journal of Petroleum)
Most reservoirs have different degree of permeability anisotropy. Optimization of recovery is crucially dependent on the reservoir quality and ansitropy. The ratio of vertical and horizontal permeability is important when reservoir anisotropy (Kv/Kh) and heterogeneity cannot be neglected. Therefore, an accurate knowledge of vertical and lateral permeability distribution is essential for better reservoir characterization.This work uses routine core data for analysis to develop new correlations and characterization of a sandstone reservoir under development. The two main goals of this study are to use core data to (1) develop correlations capable to predict vertical permeability from horizontal permeability or mean hydraulic radius and (2) develop another correlation capable to predict the permeability anisotropy ratio (Kv/Kh) using porosity data.To accomplish the objectives of this project, various petrophysical properties were experimentally measured for 112 core samples extracted from an actual sandstone reservoir. The measurements included vertical permeability, horizontal permeability, effective porosity and saturations of oil and water.The data derived were used to develop new and improved correlations capable to predict vertical permeability from horizontal permeability for the zones that were analyzed. In addition, another correlation is developed to predict anisotropy ratio from effective porosity.Applications of the developed results of this study help enhancing the prediction of vertical permeability, improving reservoir characterization and providing better simulation studies. Keywords: Vertical permeability, Anisotropic reservoir, Core data, Sandstones